Exploring student teachers' motivations and sources of confidence: the case of outdoor learning. Issue 3 (27th May 2022) - Barrable, Alexia; Touloumakos, Anna; Lapere, Linda
ABSTRACT: Outdoor learning has become an important part of policy and practice across several European contexts. While research indicates that outdoor experiences can enhance learning and mental health outcomes, studies have also identified a number of barriers to providing such experiences the most prevalent being that of teachers' confidence. Acknowledging the role of Initial Teacher Education (ITE) in preparing teachers for the demands and complexities of providing meaningful, safe and relevant outdoor learning experiences, this article explored teachers' experiences both in general, and within a one-year ITE course in Scotland, employing a qualitative methodology. In particular, semi-structured interviews were used with seven ITE students. Results yielded through thematic analysis revealed mastery experiences as being preferred, while vicarious experiences were also seen as useful. In addition, previous experiences in adulthood and childhood impact on the motivation of student teachers to teach outdoors. Implications for ITE programmes are presented.